2013
DOI: 10.1104/pp.113.219485
|View full text |Cite
|
Sign up to set email alerts
|

Enlarging Cells Initiating Apomixis inHieracium praealtumTransition to an Embryo Sac Program prior to Entering Mitosis    

Abstract: Hieracium praealtum forms seeds asexually by apomixis. During ovule development, sexual reproduction initiates with megaspore mother cell entry into meiosis and formation of a tetrad of haploid megaspores. The sexual pathway ceases when a diploid aposporous initial (AI) cell differentiates, enlarges, and undergoes mitosis, forming an aposporous embryo sac that displaces sexual structures. Embryo and endosperm development in aposporous embryo sacs is fertilization independent. Transcriptional data relating to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 71 publications
5
76
0
Order By: Relevance
“…Previous studies reported that extreme stress induces the initiation of autonomous embryo development in somatic cells in response to exogenous or endogenous signals 39 . Here we identified six nucellar embryo-associated genes that are regulated by stress, which is in agreement with a previous report on apomixis in Hieracium praealtum 40 .…”
Section: A R T I C L E Ssupporting
confidence: 81%
“…Previous studies reported that extreme stress induces the initiation of autonomous embryo development in somatic cells in response to exogenous or endogenous signals 39 . Here we identified six nucellar embryo-associated genes that are regulated by stress, which is in agreement with a previous report on apomixis in Hieracium praealtum 40 .…”
Section: A R T I C L E Ssupporting
confidence: 81%
“…Interestingly, for 14 selected meiotic genes and genes expressed in the sexual MMC no evidence for expression was found in the H. praealtum aposporous initial cell [31]. However, although the aposporous and the diplosporous initial cell both give rise to unreduced embryo sacs, cell lineage and developmental fate are markedly different.…”
Section: Resultsmentioning
confidence: 99%
“…This approach is complicated by the nature of asexual reproduction that prevents the generation of isogenic lines that differ solely with regard to reproductive mode. Nevertheless, transcriptome comparisons between apomictic and closely related sexual individuals from reproductive tissues at different developmental stages have uncovered pathways potentially central to apomixis including protein degradation, transcription, stress response, and cell-to-cell signaling (Albertini et al 2005;Laspina et al 2008;Sharbel et al 2010;Silveira et al 2012;Okada et al 2013).…”
Section: Differentially Expressed Genes Associated With Apomixismentioning
confidence: 99%